2010
DOI: 10.1093/qjmed/hcq121
|View full text |Cite
|
Sign up to set email alerts
|

Acute central nervous system infections in adults--a retrospective cohort study in the NHS North West region

Abstract: Encephalitis was as common as purulent meningitis, and HSV as common as Streptococcus pneumoniae. However, the management of patients with encephalitis was worse than meningitis. National encephalitis guidelines are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 22 publications
3
68
2
Order By: Relevance
“…Antiviral treatment was started as soon as diagnosis HSE was evoked. Still, the diagnostic delay was remarkable in our series: the median time from admission to starting antiviral treatment was 5 days in our series compared with the average of 7 h reported in immunocompetent hosts 5. The delay in diagnosis may have possibly contributed to the poor prognosis we observed.…”
Section: Discussioncontrasting
confidence: 43%
“…Antiviral treatment was started as soon as diagnosis HSE was evoked. Still, the diagnostic delay was remarkable in our series: the median time from admission to starting antiviral treatment was 5 days in our series compared with the average of 7 h reported in immunocompetent hosts 5. The delay in diagnosis may have possibly contributed to the poor prognosis we observed.…”
Section: Discussioncontrasting
confidence: 43%
“…However, in the vast majority of cases, neuronal infection does not lead to overt CNS disease (82). Viral encephalitis detection rates, even when symptoms are severe, are very low (46), due in part to the poor sensitivity of the tools used to detect infection (21). However, with the increase in the number of immunocompromised individuals, whether through increasing populations of AIDS patients or pharmacologically compromised tissue transplant recipients, there has been a concomitant increase in viral encephalitis (11,77).…”
mentioning
confidence: 99%
“…Such data are more relevant for 'point of care' clinical decision making in the acute stage, as patients do not present with a diagnostic label of 'bacterial meningitis' or 'viral encephalitis', but with a diagnostically challenging clinical syndrome of febrile meningo-encephalopathy. In a multicentre study from UK, only 20% were found to have a CNS infection out of 217 suspected patients, and CSF culture was positive in only 3 out of 199 samples [27]. In another study in UK, 60% of the cases were of unknown aetiology [30].…”
Section: Getting the Diagnosis Right -Are We Missing Something?mentioning
confidence: 94%
“…Many such series describe only microbiologically proven cases [2,3,12], and would naturally show higher isolation rates. In contrast, studies of unselected patients with presumed CNS infection have produced much lower isolation rates, even from developed countries [27,28,29,30]. Such data are more relevant for 'point of care' clinical decision making in the acute stage, as patients do not present with a diagnostic label of 'bacterial meningitis' or 'viral encephalitis', but with a diagnostically challenging clinical syndrome of febrile meningo-encephalopathy.…”
Section: Getting the Diagnosis Right -Are We Missing Something?mentioning
confidence: 99%